Investigating Learners' Conceptual Progression on pH of Solution, Acid-Base Titration, and Buffer Solutions - Santa, Eldat Wira; Sumari, Sumari; Nur, Hadi; Setiawan, Nur Candra Eka; Muntholib, Muntholib (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to explore the development of understanding of the concepts of pH, acid-base titration, and buffer solutions among 11th-grade students and 2nd- and 4th-semester university students in chemistry education. It employs a cross-sectional design using open-ended questions and interview guidelines to collect data from 153 11th-grade students, 30 second-semester university students, and 40 fourth-semester university students. The open-ended questionnaire consists of 9 items (2 questions on the pH of solutions, 4 questions on acid-base indicators and titration, and 3 questions on buffer solutions and salt hydrolysis) on a continuous scale, with an Aiken's kappa validity of 0.61 (substantial agreement) and a Cronbach's Alpha reliability (KR-20) of 0.75 (acceptable). The results indicate that scientific understanding of pH concepts, such as the pH of solutions, acid-base titration, and buffer solutions, improves with education. However, comprehension of complex concepts remains low. The study's implications highlight the need for curriculum development and the selection and implementation of learning strategies that enable students to learn in a structured, gradual, and coherent manner. Curriculum development should map out subject matter, distinguish essential from non-essential content, and organize material from simple and essential topics to more complex and non-essential ones.